Adeno-Associated Virus Technologies and Methods for Targeted Neuronal Manipulation - Haery, Leila; Deverman, Benjamin E.; Matho, Katherine S.; Cetin, Ali; Woodard, Kenton; Cepko, Connie; Guerin, Karen I.; Rego, Meghan A.; Ersing, Ina; Bachle, Susanna M.; Kamens, Joanne; Fan, Melina (Frontiers in Neuroanatomy, 2019)
Cell-type-specific expression of molecular tools and sensors is critical to construct circuit diagrams and to investigate the activity and function of neurons within the nervous system. Strategies for targeted manipulation include combinations of classical genetic tools such as Cre/loxP and Flp/FRT, use of cis-regulatory elements, targeted knock-in transgenic mice, and gene delivery by AAV and other viral vectors. The combination of these complex technologies with the goal of precise neuronal targeting is a challenge in the lab. This report will discuss the theoretical and practical aspects of combining current technologies and establish best practices for achieving targeted manipulation of specific cell types. Novel applications and tools, as well as areas for development, will be envisioned and discussed.